A low-toxic artificial fluorescent glycoprotein can serve as an efficient cytoplasmic labeling in living cell. (6th March 2015) - Si, Jiangju; Liang, Dawei; Kong, Dan; Wu, Sufang; Yuan, Lan; Xiang, Yan; Jiang, Lei
Highlights: Fluorescent labeling glycoprotein CPC was synthesized through graft copolymerization. CPC could be localized and persisted specifically in the cytoplasm of living cells. CPC was highly resistant to photo bleaching, the fluorescence was remained stable. CPC was bio-compatible and in zero grade cytotoxicity as quantified by MTT assay. Abstract: To maintain the virtue of good optical property and discard the dross of conventional fluorescent staining dyes, we provide a strategy for designing new fluorescent scaffolds. In this study, a novel fluorescent labeling glycoprotein (chitosan-poly-l -cysteine, CPC) was synthesized through graft copolymerization. CPC gives emission peak at 465–470 nm when excited at 386 nm. The submicro-scale CPC microspheres could be localized and persisted specifically in the cytoplasm of living cells, with strong blue fluorescence. Moreover, CPC was highly resistant to photo bleaching, the fluorescence was remained stable for up to 72 h as the cells grew and developed. The glycoprotein CPC was bio-compatible and in zero grade cytotoxicity as quantified by MTT assay. The fluorescent labeling process with our newly designed glycoprotein CPC is exceptionally efficient.